2022
DOI: 10.1186/s12951-022-01370-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of bio-selenium nanoparticles and sodium selenite on morpho-physiochemical attributes under normal and salt stress conditions, besides selenium detoxification pathways in Brassica napus L.

Abstract: Selenium nanoparticles (SeNPs) have attracted considerable attention globally due to their significant potential for alleviating abiotic stresses in plants. Accordingly, further research has been conducted to develop nanoparticles using chemical ways. However, our knowledge about the potential benefit or phytotoxicity of bioSeNPs in rapeseed is still unclear. Herein, we investigated the effect of bioSeNPs on growth and physiochemical attributes, and selenium detoxification pathways compared to sodium selenite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 103 publications
(112 reference statements)
4
26
0
2
Order By: Relevance
“…Equally, Rossatto et al (2017) reported that reverse transcription quantitative PCR (RT-qPCR) revealed higher expression levels of CAT, APX, and SOD, which detoxified ROS in rice plants to alleviate NaCl toxicity. Moreover, the data of the present research regarding the modulation of the expression levels of POD, CAT, APX, and SOD are in agreement with the findings of El-Badri et al (2022b). They reported that modulations in the transcript levels of these antioxidant genes enhanced the activity of the respective antioxidant enzymes to induce salt tolerance by scavenging ROS in B. napus plants.…”
Section: Discussionsupporting
confidence: 91%
“…Equally, Rossatto et al (2017) reported that reverse transcription quantitative PCR (RT-qPCR) revealed higher expression levels of CAT, APX, and SOD, which detoxified ROS in rice plants to alleviate NaCl toxicity. Moreover, the data of the present research regarding the modulation of the expression levels of POD, CAT, APX, and SOD are in agreement with the findings of El-Badri et al (2022b). They reported that modulations in the transcript levels of these antioxidant genes enhanced the activity of the respective antioxidant enzymes to induce salt tolerance by scavenging ROS in B. napus plants.…”
Section: Discussionsupporting
confidence: 91%
“…The Sclerospora graminicola biosynthesized Se-NPs inhibit vegetative growth, sporulation, spore viability, and proliferation [ 36 ]. El Badri et al [ 37 ] synthesized biogenic Se-NPs (bio Se-NPs) with sizes ranging from 120 to 260 nm, with a mean size of 167 nm. Six species of Trichoderma were examined for their ability to produce Se-NPs, including T. asperellum , T. harzianum , T. atroviride , T. virens , T. longibrachiatum , and T. brevicompactum .…”
Section: Modes Of Senp Synthesismentioning
confidence: 99%
“…Se salt (sodium selenite, 5 mg/L treatment) resulted in 92% increase in the TS-5 variety compared to untreated sesame plants. 24 Badri et. al found that bio-synthesized SeNPs and sodium selenite had opposite effects on B. napus under normal and stress conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The highest proline accumulation of 111.1% was observed in the TS-5 variety followed by TH-6 (92.6%) and Til-18 (89.2%), as shown in Figure . Se salt (sodium selenite, 5 mg/L treatment) resulted in 92% increase in the TS-5 variety compared to untreated sesame plants . Badri et.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation